Who or what is 'the public' in critical public health? Reflections on posthumanism and anthropological engagements with One Health. Issue 3 (27th May 2017) - Rock, Melanie J.
Abstract: This paper extends the terms of engagement between social science, posthumanist debates and One Health by questioning whether 'the public' may include non-human animals. The One Health concept refers to interdependence between human beings and non-human species in socio-ecological systems. One Health interventions and critiques have tended to emphasize the prevention of zoonotic infections, whereas this paper reflects on more than a decade of engaged research in One Health promotion. Repeatedly, this particular approach to One Health promotion has highlighted the imprint of multi-species entanglements in public life, especially the problematization and politicization of people's pets. Serious consideration for multi-species entanglements cautions against conflating 'the public' with human beings and human interests, to the exclusion of all others. Human beings have never lived separate and apart from non-human species, and we all depend on shared environments. To do justice to multi-species entanglements, socio-ecological theory should undergo expansion in health promotion.